PROFIL PENYESUAIAN SOSIAL PADA SISWA KELAS VII SMP - Rosmayanti; Asep Samsudin; Williya Novianti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Social adjustment is an individual's ability to adapt to their surrounding environment, both in relation to other individuals and social groups. Individuals who are able to adjust socially are more likely to build positive social relationships within the school environment. Conversely, those with low social adjustment often face difficulties in socializing, communicating, collaborating with others, and tend to lack sensitivity to their social surroundings. Therefore, it is important for every student to develop adequate social adjustment skills in the school setting.This study aims to examine the social adjustment profile of seventh-grade students at SMP YP Mustika Padalarang, with the objective of supporting students in adapting to their environment, particularly at school. The research employed a mixed methods approach using a sequential explanatory design. The sampling technique used in this study was simple random sampling, involving 154 seventh-grade students.The results indicate that, in general, students’ social adjustment falls into the moderate category. This means that students possess basic social skills but have not yet demonstrated consistency in applying them across various situations. These students require further support and training in aspects such as communication, empathy, and conflict resolution. The findings of this study are expected to serve as preliminary data for school counselors or other researchers to design interventions that support the improvement of students’ social adjustment, and to complement and strengthen previous research.